Effects of penetrating captive bolt gun model and number of stuns on stunning-related variables of cattle in a commercial slaughter facility - Casagrande, Renan, author; Edwards-Callaway, Lily, advisor; Hess, Tanja, advisor; Grandin, Temple, committee member; Wagner, John, committee member; Sharp, Benjamin, committee member (Colorado State University. Libraries, 2021)
The objective of this study was to assess two different penetrating captive bolt gun models (Jarvis USSS-1 and USSS-21) and two stunning methods (1KNOCK and 2KNOCK, applying one and two knocks, respectively) on stunning-related variables in cattle. Heads were collected at a commercial slaughter facility and knocking efficiency, knock hole diameter, brain damage, knock hole placement and hemorrhage were assessed. Knocking efficiency was not impacted by gun model or number of knocks (P = 0.39 and 0.12, respectively). Knock number influenced knock hole diameter, brain damage and hemorrhage in the cavity (P ≤ .01). Presence of brainstem damage was greater (P < .01) when using the USSS-21 gun. Results suggested similar performance between the USSS-1 and USSS-21 gun models. Potential benefits of using the newest model could be related to damaging vital brain areas like the brainstem.